Excitation function for the Al27(d,αp) Na24 reaction between 0 and 28.1 Mev - Lenk, P. A.; Slobodorian, Rodolfo J. (American Physical Society, 1959)
Fil: Lenk, P. A. Comisión Nacional de Energía Atómica; Argentina